Exploring the Mandalagiri Coffee Supply Chain Using the Business Model Canvas (BMC) to Achieve Sustainability in the Coffee Industry - Hamdani, Nizar Alam; Rismanto, Hilman; Basit, Acep Abdul (Ilomata International Journal of Management, 2026)
This study explores the Mandalagiri coffee supply chain using the Business Model Canvas (BMC) approach to support sustainability in the coffee industry. The research is motivated by increasing competition in both domestic and international markets, as well as the need for small and medium coffee industries to strengthen competitiveness through innovative, efficient, and sustainable business strategies. The novelty of this study lies in mapping coffee management from upstream to downstream while expanding market access through professional collaboration with local and international buyers. A mixed-methods approach was used, combining in-depth interviews, field observations, Focus Group Discussions (FGDs), and questionnaires administered to 40 respondents, including farmers, business actors, village governments, and related stakeholders. Qualitative analysis applied the Resource-Based View (RBV) framework, emphasizing VRIO (valuable, rare, inimitable, and organizational) resources, while quantitative analysis employed Structural Equation Modeling–Partial Least Squares (SEM-PLS) 4.0. The findings reveal a strong relationship between RBV and sustainability with a coefficient of 0.794, supported by a t-statistic of 16.921, indicating a significant positive effect. This demonstrates that stronger RBV characteristics enhance sustainability outcomes. Within the BMC, key partners, key resources, and value propositions play a crucial role in improving competitive advantage through strengthened human resources, product innovation, and reputation. Overall, the study confirms that coffee industry sustainability depends not only on external strategic efforts but also on effective internal resource management. The results are expected to serve as a reference for developing competitive coffee business models oriented toward economic, social, and environmental sustainability.